Market perception of efficient light source technologies: a case study on sustainable energy transitions in Sri Lanka. (17th November 2021) - Jayaratne, W.; Dasanayaka, S.W.S.B.; Serhan, Omar Al; Alam, Isra A.; Samara, Fatin
Developing countries are transitioning towards more sustainable practices with the hopes of increasing energy efficiency and savings. A conceptual model, questionnaire surveys and structured interviews were used to assess the current situation of the Sri Lankan market on their perceptions towards transitioning to light emitting diodes (LEDs). The results of the study suggested that the main key factors influencing choices on artificial lighting included: high price, size, limited LEDs knowledge, low intervention of apex bodies, and individual perceptions of the technology. Regardless of the multiple benefits of LEDs, customer acceptance for LED solutions was minimal in comparison to other emerging energy technologies and lighting solutions. This paper suggests that energy policy related apex bodies should incorporate some incentives to popularise LED solutions in the market. The methodology employed and the recommendations derived can be used as guidelines to similar types of energy-related green research in the developing nations.